2007
DOI: 10.1021/la700892z
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Ordered Membrane Domains by GPI-Anchored Intestinal Alkaline Phosphatase

Abstract: Glycosylphosphatidyl-inositol (GPI)-anchored proteins preferentially localize in the most ordered regions of the cell plasma membrane. Acyl and alkyl chain composition of GPI anchors influence the association with the ordered domains. This suggests that, conversely, changes in the fluid and in the ordered domains lipid composition affect the interaction of GPI-anchored proteins with membrane microdomains. Validity of this hypothesis was examined by investigating the spontaneous insertion of the GPI-anchored in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 67 publications
2
18
0
3
Order By: Relevance
“…For all samples, AFM showed that BIAP spontaneously inserted in the gel, i.e. highly ordered, phase of bilayers [67,68,40]. This spontaneous BIAP insertion into SLBs was in accordance with the observations reported for the insertion of various GPI proteins into biomembranes (see above).…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainssupporting
confidence: 91%
See 4 more Smart Citations
“…For all samples, AFM showed that BIAP spontaneously inserted in the gel, i.e. highly ordered, phase of bilayers [67,68,40]. This spontaneous BIAP insertion into SLBs was in accordance with the observations reported for the insertion of various GPI proteins into biomembranes (see above).…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainssupporting
confidence: 91%
“…Finally, differences between fluorescence and AFM data might be related to the pronounced effect of scanning forces on AP-GPI visualization. As recently reported [40], the use of scanning forces higher than 300 pN resulted in the extraction of a large number of BIAP molecules from the ordered domains (Fig. 5).…”
Section: Interaction Of Ap-gpi With Ordered Gel Domainssupporting
confidence: 76%
See 3 more Smart Citations